1999
DOI: 10.1056/nejm199901143400204
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Supplements for the Prevention of Colorectal Adenomas

Abstract: Calcium supplementation is associated with a significant - though moderate - reduction in the risk of recurrent colorectal adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
493
4
22

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 791 publications
(535 citation statements)
references
References 36 publications
16
493
4
22
Order By: Relevance
“…Two intervention trials conducted on adenoma recurrence found a beneficial effect 13,15 of calcium supplementation, although it was significant in only 1 trial. 13 A more recent analysis found that a stronger beneficial effect of calcium supplementation on the risk of recurrence with advanced neoplasms than with tubular adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two intervention trials conducted on adenoma recurrence found a beneficial effect 13,15 of calcium supplementation, although it was significant in only 1 trial. 13 A more recent analysis found that a stronger beneficial effect of calcium supplementation on the risk of recurrence with advanced neoplasms than with tubular adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…13 A more recent analysis found that a stronger beneficial effect of calcium supplementation on the risk of recurrence with advanced neoplasms than with tubular adenomas. 14 The effect was greater for subjects with a high dietary calcium intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium is hypothesized to prevent carcinogenesis in the colon by either binding bile acids and or fatty acids in the lumen or by having a direct inhibitory effect of the proliferation of the epithelial cells in the colon. The randomized controlled trial which assessed the efficacy of calcium supplementation on the risk of new colon adenoma formation amongst individuals with history of adenomas has revealed reduced incidence of adenomas apparent after just 1 year of supplementation 24 .…”
Section: Obesity and Colorectal Cancermentioning
confidence: 99%
“…Progress has been slow, however, in defining specific dietary interventions to reduce the risk (Greenberg et al, 1994;MacLennan et al, 1995;Baron et al, 1999;Alberts et al, 2000;Bonithon-Kopp et al, 2000;Schatzkin et al, 2000). This may have been a consequence of the cumbersome method that has been used to test possible interventions.…”
mentioning
confidence: 99%